1990
DOI: 10.1152/ajpcell.1990.259.6.c940
|View full text |Cite
|
Sign up to set email alerts
|

Na-H exchange in myocardium: effects of hypoxia and acidification on Na and Ca

Abstract: Historically, increase in cell Na content during ischemic and hypoxic episodes were thought to result from impaired ATP production causing decreased Na(+)-K(+)-ATPase activity. Here we report the results of testing the alternate hypothesis that hypoxia-induced Na uptake is 1) the result of increased entry, as opposed to decreased extrusion 2) via Na-H exchange operating in a pH regulatory capacity and that cell Ca accumulation occurs via Na-Ca exchange secondary to collapse of the Na gradient. We used 23Na-, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
98
3
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(116 citation statements)
references
References 23 publications
13
98
3
2
Order By: Relevance
“…Several studies have shown that the attenuation of the rise in EDP by interventions is linked to the maintenance of intracellular sodium and calcium homeostasis [44][45][46][47][48][49]. In our earlier studies, we have shown that inhibition of aldose reductase attenuated the rise in intracellular sodium and calcium during ischemia and reperfusion in Type 1 BB/WOR diabetic hearts [48].…”
Section: Discussionmentioning
confidence: 80%
“…Several studies have shown that the attenuation of the rise in EDP by interventions is linked to the maintenance of intracellular sodium and calcium homeostasis [44][45][46][47][48][49]. In our earlier studies, we have shown that inhibition of aldose reductase attenuated the rise in intracellular sodium and calcium during ischemia and reperfusion in Type 1 BB/WOR diabetic hearts [48].…”
Section: Discussionmentioning
confidence: 80%
“…When the internal pH of cardiac cells is lowered, as occurs during ischemia and hypoxia, Na ϩ /H ϩ exchange becomes the major regulatory system by which cells recover from acidosis (25). Accumulation of H ϩ has been shown to mediate a rise in Na ϩ by activation of the Na ϩ /H ϩ exchanger (3,25). Inhibition of the Na ϩ /K ϩ -ATPase activity during hypoxia markedly increases Na ϩ accumulation (3).…”
Section: Discussionmentioning
confidence: 99%
“…The methods used were modified from those previously reported (3,6,31). Briefly, 12-to 13-wk-old ovariectomized Sprague-Dawley rats (OVX) were purchased from Charles River 1 wk after ovariectomy.…”
Section: Generalmentioning
confidence: 99%
“…This method measures Na i ϩ as an amount, and to minimize assumptions, we report it as such. [Ca 2ϩ ]i (in nmol/l cytosolic water) was calculated as the product of the Ca 2ϩ -FBAPTA dissociation constant (Kd) and the ratio of the areas of the Ca 2ϩ -bound and Ca 2ϩ -free peaks in the FBAPTA spectrum (6). The Kd for Ca 2ϩ -FBAPTA was 294 nM.…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation